Effect of N-Acetylcysteine on Antioxidant Defense, Oxidative Modification, and Salivary Gland Function in a Rat Model of Insulin Resistance. (30th January 2018) - Żukowski, Piotr; Maciejczyk, Mateusz; Matczuk, Jan; Kurek, Krzysztof; Waszkiel, Danuta; Żendzian-Piotrowska, Małgorzata; Zalewska, Anna
Abstract : Oxidative stress plays a crucial role in the salivary gland dysfunction in insulin resistance (IR). It is not surprising that new substances are constantly being sought that will protect against the harmful effects of IR in the oral cavity environment. The purpose of this study was to evaluate the effect of N-acetylcysteine (NAC) on oxidative stress and secretory function of salivary glands in a rat model of insulin resistance. Rats were divided into 4 groups: C—normal diet, C + NAC—normal diet + NAC, HFD—high-fat diet, and HFD + NAC. We have demonstrated that NAC elevated enzymatic (superoxide dismutase, catalase, and peroxidase) and nonenzymatic antioxidants (reduced glutathione (GSH) and total antioxidant capacity (TAS)) in the parotid glands of HFD + NAC rats, while in the submandibular glands increased only GSH and TAS levels. NAC protects against oxidative damage only in the parotid glands and increased stimulated salivary secretion; however, it does not increase the protein secretion in the both salivary glands. Summarizing, NAC supplementation prevents the decrease of stimulated saliva secretion, seen in the HFD rats affected. NAC improves the antioxidative capacity of the both glands and protects against oxidative damage to the parotid glands of IR rats.